Engineering Silk Protein to Modulate Polymorphic Transitions for Green Lithography Resists - Chung, Soon Chun; Park, Joon Song; Jha, Rakesh Kumar; Kim, Jieun; Kim, Jinha; Kim, Muyoung; Choi, Juwan; Kim, Hongdeok; Park, Da Hye; Gogurla, Narendar; Lee, Tae Yun; Jeon, Heonsu; et al. (ACS Applied Materials and Interfaces, 2022)
Silk protein is being increasingly introduced as a prospective material for biomedical devices. However, a limited locus to intervene in nature-oriented silk protein makes it challenging to implement on-demand functions to silk. Here, we report how polymorphic transitions are related with molecular structures of artificially synthesized silk protein and design principles to construct a green-lithographic and high-performative protein resist. The repetition number and ratio of two major building blocks in synthesized silk protein are essential to determine the size and content of β-sheet crystallites, and radicals resulting from tyrosine cleavages by the 193 nm laser irradiation induce the β-sheet to α-helix transition. Synthesized silk is designed to exclusively comprise homogeneous building blocks and exhibit high crystallization and tyrosine-richness, thus constituting an excellent basis for developing a high-performance deep-UV photoresist. Additionally, our findings can be conjugated to design an electron-beam resist governed by the different irradiation−protein interaction mechanisms. All synthesis and lithography processes are fully water-based, promising green lithography. Using the engineered silk, a nanopatterned planar color filter showing the reduced angle dependence can be obtained. Our study provides insights into the industrial scale production of silk protein with on-demand functions.
Keywords: Biomedical devices; Building blockes; Demand function; Green photoresist; On demands; Polymorphic transitions; Prospectives; Silk proteins; Synthesised; Synthetic biology; Molecular Structure; Protein Conformation, alpha-Helical; Protein Conformation, beta-Strand; Silk; green photoresist; lithography; polymorphic transition; silk protein; synthetic biology